Hildegard of Bingen : Solutions to Thirty-Eight Questions - Hildegard, Saint, 1098-1179 (Book collections on Project MUSE., 2014)
Perhaps the least studied of HIldegard of Bingen's writings, Solutions to Thirty-Eight Questions is translated in this volume into English for the first time from the original Latin. In this work of exegesis, Hildegard (1098-1179) resolves thorny passages of Scripture, theological questions, and two issues in hagiographic texts. Solutions to Thirty-Eight Questions joins Hildegard's Homilies on the Gospels, which were directed to her nuns, as evidence of the seer's exegetical writing as well as her authority as an exegete. The twelfth-century saint wrote in standard genres of exegesis--homilies and solutiones--and her interpretations of Scripture were widely sought, including by male audiences. (back cover).